Long-term evaluation of crown and root discoloration induced by different endodontic sealers - Beatriz Serrato Coelho; Paula Pontes Garcia; Flávia Sens Fagundes Tomazinho; Leonardo Fernandes Cunha; Denise Piotto Leonardi; Carla Castiglia Gonzaga; Marilisa Carneiro Leão Gabardo; Flares Baratto-Filho (Universidade Estadual de Campinas, 2018)
Aim: To evaluate crown and root discoloration promoted by different endodontic sealers after root canal filling. Methods: Eighty bovine incisors were prepared and filled with: Endofill, Sealer 26, AH Plus, and MTA Fillapex. Color was recorded using a spectrophotometer before endodontic treatment (T0) and at 24 hours (T1), seven days (T2), 30 days (T3), and 90 days (T4) after treatment. Analyses were performed on the middle and cervical regions of the crown, and on the cervical third of the root, immediately below the cementoenamel junction. The color alterations (ΔE) were calculated using Commission International de I'Eclairage (CIE) L*a*b parameters, and data were analyzed by analysis of variance (ANOVA) and Tukey's test (p<0.05). Results: All sealers induced color alterations. Sealer 26 resulted in the smallest changes in color (E = 5.32). The other materials did not present statistical differences (AH Plus E = 6.98; MTA Fillapex E = 6.88; Endofill E = 6.41). Of the three regions analyzed, the largest discoloration was observed at the cervical third of the root (E=10.67). In terms of time, the largest ΔE values (E=7.72) were observed at T4. Color changes at T1 (E=5.88), T2 (E=6.10), and T3 (E=5.89) were statistically similar. Conclusions: All endodontic sealers promoted discoloration on the tooth crown and root.